Simulation of bond prices - Artamonova, Jelena (Lietuvos matematikos rinkinys, 2005)
In this paper we introduce the estimation technique for the parameters of the bond pricing model. The proposed methods are illustrated by the Lithuanian Government securities. The results show that a squared binomial (two-factor) bond market model approximates the bond prices more precisely than analogous quadronomial (one-factor) model.
Keywords: bond market; squared binomial model; quadronomial model